A Network of Regulations by Small Non-Coding RNAs: The P-TEFb Kinase in Development and Pathology - Ghanbarian, Hossein; Grandjean, Valerie; Cuzin, Francois; Rassoulzadegan, Minoo (Frontiers in Genetics, 2011)
Part of the heterodimeric P-TEF-b element of the Pol II transcription machinery, the cyclin-dependent kinase 9 plays a critical role in gene expression. Phosphorylation of several residues in the polymerase is required for elongation of transcript. It determines the rates of transcription and thus, plays a critical role in several differentiation pathways, best documented in heart development. The synthesis and activity of the protein are tightly regulated in a coordinated manner by at least three non-coding RNAs. First, its kinase activity is reversibly inhibited by formation of a complex with the 334 nt 7SK RNA, from which it is released under conditions of stress. Then, heart development requires a maximal rate of synthesis during cardiomyocyte differentiation, followed by a decrease in the differentiated state. The latter is insured by microRNA-mediated translational inhibition. In a third mode of RNA control, increased levels of transcription are induced by small non-coding RNA molecules with sequences homologous to the transcript. Designated paramutation, this epigenetic variation, stable during development, and hereditarily transmitted in a non-Mendelian manner over several generations, is thought to be a response to the inactivation of one of the two alleles by an abnormal recombination event such as insertion of a transposon.